8th Grade Students’ Understanding Level and Misconceptions about Key Concepts of Citizenship (Sample of Kastamonu) - Faiz, Melike; Ergin, Esma (Elsevier BV, 2014)
AbstractThe purpose of this study is to find out eight grade (age 13-14) students understanding level and misconceptions about citizenship study concepts such as citizens, judiciary, law, legislature, election, constitution, independence, republic, democracy, government, governance, sovereignty, nation, national sovereignty, and national culture. Because of these concepts are in 7th grade curriculum concepts the study applied in 8th grade for assessing students understanding level and misconceptions about these key concepts which learned in advance. The sample is 150 eight grade students who are studying in a school which located in the centre of Kastomonu, in 2011-2012 educational term These students are studying in the same school but five different classes in the same level (eight grade). A semi-constructed survey which contains 15 open ended questions are used as a data collection. The survey is modified from Gülüm's (2010) study. The data’ from the study are analyzed by using descriptive survey model and interpreted by authors. The answers of 15 open ended question which created by researchers analyzed under four categories such as full understanding, some understanding, misconception and never understanding. The research constructed up on students ‘understanding level and differences’ between genres and classes. At the end of the research by analyzing the data we find out; Primary level eight grade students in Kastamonu have a low understanding and some misconceptions. There is no difference about understanding these concepts between genres and classes but in general all students have a low understanding and some misconceptions.
Keywords: democracy; Social Studies; independence; government; national sovereignty; election; nation; sovereignty; legislature; constitution; republic; the concept; citizens; governance; and national culture; judiciary; law; 4. Education; 16. Peace & justice